Analisis Perbandingan Enkripsi File Teks Berformat .txt dan .docx Menggunakan Algoritma AES - Limartha, Kennardy Andrew; Arta Wibawa, I Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 2 (2025): JNATIA Vol. 3, No. 2, Februari 2025DO - 10.24843/JNATIA.2025.v03.i02.p10, 2025)
In this research, the Advanced Encryption Standard (AES) algorithm is used to encrypt text files. Data stored in various formats has the potential to cause the size of the data on the data storage device to become large and does not necessarily guarantee the security of the data. One method of data security is to encrypt data. This research utilizes data in text file format with data types in the form of ".txt" and ".docx" which refer to the file size for testing. Based on the test results, it shows that the AES encryption method provides good results for text file formats. The time required for the encryption process using the AES algorithm is influenced by each different file size, the larger the file size used, the longer the computing time required and vice versa.